To the Question of Academic Drawing and its Place in Training the Arts Specialists - I. E. Smirnova; Y. K. Abayev (Russian State Vocational Pedagogical University, 2015)
The paper is devoted to methodology problems concerning the higher art school training. The authors emphasize the role of academic drawing in educational process, its impact on developing the substantive perception and professional thinking of architects and designers, and the importance of fundamental assignments for the training quality assurance. The skill of academic graphics is a prime necessity for any artwork and architecture project. Both the designers and architects use the academic drawing asan instrument for convincing presentations of their concepts and plans. The developed skill of academic drawing can be achieved by means of the verified training techniques, given the adequate amount of time allocated for mastering the skill.The paper singles out the negative trends in modern designers and architects' training: insufficient attention to the course of academic drawing in educational plans and curricula, ignoring the strict methodological sequence of academic assignments, violation of didactic principles, cutting down the academic hours, lack of psychological and pedagogical training received by the art teachers.In conclusion, the authors give a number of methodological recommendations that might be of interest to the curricula developers and teachers of the higher art schools, art faculties and departments.